2007
DOI: 10.1096/fasebj.21.5.a423-d
|View full text |Cite
|
Sign up to set email alerts
|

Sorting nexin‐25, a novel member of the dopamine receptor signalplex, up‐regulates D 1 and D 2 dopamine receptor expression in HEK293 cells

Abstract: Dopamine receptors (DARs) do not exist as singular independent units within the synaptic membrane, but are part of large macromolecular complexes of interacting proteins. These interacting proteins influence the receptor in a variety of ways. Our current studies employ a co‐immunoprecipitation assay for DARs from transfected cell lines, coupled with mass spectrometry sequencing to identify interacting partners. One protein identified this way was sorting nexin‐25 (SNX25). Mammalian SNXs have been suggested to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…SNX25 also regulates D 1 R in the kidney. Overexpression of Snx25 in HEK 293 cells heterologously expressing D 1 R and D 2 R increases the expression of D 1 R and D 2 R, activates the downstream molecules, and disturbs the endocytosis and recycling of D 2 R. Conversely, the expression of D 1 R and D 2 R is reduced in cells lacking Snx25 [83,84]. Thus, current studies show that renal D 1 R is regulated by some SNXs, specifically SNX5, SNX19, and SNX25.…”
Section: Regulation Of Blood Pressure By Snxsmentioning
confidence: 85%
See 1 more Smart Citation
“…SNX25 also regulates D 1 R in the kidney. Overexpression of Snx25 in HEK 293 cells heterologously expressing D 1 R and D 2 R increases the expression of D 1 R and D 2 R, activates the downstream molecules, and disturbs the endocytosis and recycling of D 2 R. Conversely, the expression of D 1 R and D 2 R is reduced in cells lacking Snx25 [83,84]. Thus, current studies show that renal D 1 R is regulated by some SNXs, specifically SNX5, SNX19, and SNX25.…”
Section: Regulation Of Blood Pressure By Snxsmentioning
confidence: 85%
“…In hRPTCs, SNX19 colocalizes with D 1 R in the cytoplasm and at the plasma membrane; activation of D 1 Rs with fenoldopam causes their endocytosis [80]. In the basal state, in the mouse kidney, as in hRPTCs, the colocalization between SNX19 and D 1 R is also observed at the plasma membrane of renal proximal tubules (RPTs); the intravenous infusion of fenoldopam increased the colocalization of SNX19 [83,84]. Thus, current studies show that renal D 1 R is regulated by some SNXs, specifically SNX5, SNX19, and SNX25.…”
Section: Snx-mediated Regulation Of Renal D 1 Rmentioning
confidence: 99%
“…Furthermore, it has been reported that SNX25 overexpression is associated with increased expression levels and signaling of D 1 R [ 54 ]. Another study has indicated that SNX5 depletion can result in hypertension in normotensive mice [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…SNX25 is expressed in many tissues, including the kidney [ 106 ]. The overexpression of SNX25 amplifies the expression of D 1 R and D 2 R. Additionally, it augments signaling mediated by D 2 R and disrupts the endocytosis and recycling of D 2 R [ 106 ] However, it does not affect D 1 R desensitization [ 106 , 107 ]. SNX27 is involved in D 2 R activation of G protein-gated inwardly rectifying channels in the brain [ 108 ].…”
Section: Renal D2-like Receptors and Lipid Raftsmentioning
confidence: 99%